2016
DOI: 10.1371/journal.ppat.1005852
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniavirus-Dependent Metastatic Leishmaniasis Is Prevented by Blocking IL-17A

Abstract: Cutaneous leishmaniasis has various outcomes, ranging from self-healing reddened papules to extensive open ulcerations that metastasise to secondary sites and are often resistant to standard therapies. In the case of L. guyanensis (L.g), about 5–10% of all infections result in metastatic complications. We recently showed that a cytoplasmic virus within L.g parasites (LRV1) is able to act as a potent innate immunogen, worsening disease outcome in a murine model. In this study, we investigated the immunophenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 65 publications
2
88
0
3
Order By: Relevance
“…The importance of IFN-γ was further demonstrated as a critical component of our murine model for metastatic leishmaniasis, where IFN-γ −/− mice failed to control Lgy infection, causing multiple metastatic lesions, usually located on the tail (17). In this model, metastases were accelerated in the presence of the endogenous LRV1 within Lgy parasites.…”
Section: Viral Coinfection Modulates Macrophage Responsiveness To Ifn-γmentioning
confidence: 89%
See 3 more Smart Citations
“…The importance of IFN-γ was further demonstrated as a critical component of our murine model for metastatic leishmaniasis, where IFN-γ −/− mice failed to control Lgy infection, causing multiple metastatic lesions, usually located on the tail (17). In this model, metastases were accelerated in the presence of the endogenous LRV1 within Lgy parasites.…”
Section: Viral Coinfection Modulates Macrophage Responsiveness To Ifn-γmentioning
confidence: 89%
“…These findings may explain why the tight correlation between disease severity and metastasis with LgyLRV1 + in animal models (5) may be more variable in humans (13,17,47,48). Potentially, coinfection with viruses or other pathogens inducing a sufficient amount of type I IFNs could increase the severity of Lgy infection, contributing to the development of more severe disease manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assignment of the LRV1 specificity of these phenotypes benefited greatly from the availability of a single isogenic LRV1-free line of Lgy (12). Importantly, recent studies have shown that disease severity is increased in patients infected with LRV1 + Lgy, relative to LRV1-negative parasites (13).…”
mentioning
confidence: 99%